2008
DOI: 10.1093/humrep/den279
|View full text |Cite
|
Sign up to set email alerts
|

Semen donors in Germany: A study exploring motivations and attitudes

Abstract: One-third of the donors supported parental disclosure and just under half of the donors are willing to be identifiable, despite a climate and history of secrecy. This study indicates that there are donors who are agreeable to be part of the move away from secrecy, and this will have implications for professionals involved in providing DI services in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 9 publications
3
25
0
1
Order By: Relevance
“…Donation of unused embryos may offer an acceptable option both for relinquishing couples and for some patients who currently consider oocyte donation in another country. Furthermore, medical guidelines regarding the treatment of lesbian and single women [51] and legislation pertaining to the legal status of donors could be altered so that guidelines are not more restrictive than current legislation and donors are exempted from legal responsibility, independent from the civil status or the sexual orientation of the recipient (for a detailed explanation of this issue see: [52] [59]. These regulations and conventions, though ratified by only some European countries and subject to variable acceptance, can contribute to, or serve as, a basis for minimum standards of care on the bioethical principles of justice, autonomy and benevolence of all parties in CBRS including the welfare of any offspring.…”
mentioning
confidence: 99%
“…Donation of unused embryos may offer an acceptable option both for relinquishing couples and for some patients who currently consider oocyte donation in another country. Furthermore, medical guidelines regarding the treatment of lesbian and single women [51] and legislation pertaining to the legal status of donors could be altered so that guidelines are not more restrictive than current legislation and donors are exempted from legal responsibility, independent from the civil status or the sexual orientation of the recipient (for a detailed explanation of this issue see: [52] [59]. These regulations and conventions, though ratified by only some European countries and subject to variable acceptance, can contribute to, or serve as, a basis for minimum standards of care on the bioethical principles of justice, autonomy and benevolence of all parties in CBRS including the welfare of any offspring.…”
mentioning
confidence: 99%
“…This development could optimize IVF treatment, but make men literally obsolete from the reproductive process. The potential stigma produced (Thorn et al, 2008) by this development remains for the moment little interrogated, and awaits future research.…”
Section: Resultsmentioning
confidence: 99%
“…In a study concerning 63 German donors, 19% considered the national limit of 15 offspring per donor appropriate, 11% considered it too high and 27% too low (43% had no opinon), (Thorn et al, 2008). A recent survey among 21 sperm donors registered with a UK-based DNA-based voluntary contact registry showed that most sperm donors (13) imposed no limit on the maximum number of offspring conceived with their gametes and one would accept 'more than 20', whereas four would feel comfortable with five to 10 offspring and one fewer than five (van den Akker et al, 2015).…”
Section: Psychosocial Considerationsmentioning
confidence: 99%